Mesenchymal Stem Cell-Based Therapy for Kidney Disease: A Review of Clinical Evidence - Anna Julie Peired; Alessandro Sisti; Paola Romagnani (Hindawi Limited, 2016)
Mesenchymal stem cells form a population of self-renewing, multipotent cells that can be isolated from several tissues. Multiple preclinical studies have demonstrated that the administration of exogenous MSC could prevent renal injury and could promote renal recovery through a series of complex mechanisms, in particular via immunomodulation of the immune system and release of paracrine factors and microvesicles. Due to their therapeutic potentials, MSC are being evaluated as a possible player in treatment of human kidney disease, and an increasing number of clinical trials to assess the safety, feasibility, and efficacy of MSC-based therapy in various kidney diseases have been proposed. In the present review, we will summarize the current knowledge on MSC infusion to treat acute kidney injury, chronic kidney disease, diabetic nephropathy, focal segmental glomerulosclerosis, systemic lupus erythematosus, and kidney transplantation. The data obtained from these clinical trials will provide further insight into safety, feasibility, and efficacy of MSC-based therapy in renal pathologies and allow the design of consensus protocol for clinical purpose.